Revolutionizing Islamic Curriculum in Enabling Sustainable Futures through SDGs - Hani Atul Khoiriyah (Al-Qalam Institue, 2024)
This study aims to explore and enhance the integration of the United Nations Sustainable Development Goals (SDGs) into Islamic education curricula, which is rooted in values such as justice, stewardship, and social welfare. Despite the global recognition of education as a key driver for sustainable development, the incorporation of SDGs into Islamic education remains underdeveloped. Through qualitative analysis and phenomena studies in Indonesia, Nigeria, Pakistan, and Saudi Arabia. Data were collected based on literature descriptions from national and international research results. This study identifies examples of successful SDGs integration and challenges that still exist, including resistance to change, resource constraints, and lack of understanding of the SDGs. The findings contribute to the development of a framework for embedding SDG content within Islamic curricula, advocating for active learning methods and collaboration with international organizations to exchange best practices. This research not only bridges the gap between Islamic principles and SDGs but also provides a foundation for more effective and sustainable implementation in Islamic educational institutions globally.